E-AUCTION SYSTEM USING MOBILE AGENT TECHNOLOGY - ABDUL RAZAK, NURAFIDAH (Universiti Teknologi Petronas, 2005)
Mobile agent technology has known an important rise these last years. This project will present 3 objectives in constructing an E-Auction system which are; to study on how mobile agent system is said to be useful to reduce communication cost in e-auction system as well as to accept the use of limited local resources, and to have an asynchronous computing. Instead of having to surf endlessly through the WWW (World Wide Web) and digesting huge amounts of possibly untrustworthy information, personalized mobile agents autonomously gather information about the item user want to buy. Once they have found the destination or server, the piece of software or the latest hit single which user looking for, the agent can send the result of the best requested item on behalf of the user. This project will be focusing on E-Auction business on PDA's and will be using mobile agent platform which is aglets, Java runtime, and J2sdkl.4.1_03. This project will undergo 5 stages which are; plan the hardware or software required for the project, then analyze and get Product Requirement, next is design the process of implementing PDA's E-Auction System, implement the project by using mobile agent platform - aglets that involves programming activity and last is to test the product to ensure the product successfully completed and satisfy and fulfill the objectives of this project. The result and discussion about the system produced will highlights how the system works generally .Some other interested formula and idea from other project's discussion will also be used to further doing this project. As a conclusion, this project is aimed to create a simple E-Auction system using mobile agent technology and need to be improved in many aspects and that can be the recommendation for future work for expansion and continuation.